THE CHRISTIAN EDUCATION APPROACH IN GUIDING THE DIGITAL GENERATION TO ADDRESS SOCIAL MEDIA AND TOXIC BEHAVIOR - Zalukhu, Amirrudin (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2025)
The rapid expansion of social media has introduced both opportunities and challenges, particularly for the digital generation. Toxic behaviors such as cyberbullying, hate speech, and cancel culture have emerged as significant concerns, impacting mental health and social relationships. This study explores how Christian education can guide the digital generation in addressing these toxic behaviors by integrating core values like love, empathy, forgiveness, and self-control. Using a qualitative literature review approach, this research examines theoretical perspectives and case studies highlighting the role of Christian teachings in fostering ethical online behavior and promoting digital responsibility. The findings reveal that Christian education provides a transformative framework for equipping youth with the moral and spiritual tools necessary to navigate the complexities of social media.